Church Contextual Factors Associated With Latinx Physical Activity and Park Use. Issue 3 (7th July 2022) - Perez, Lilian G.; Cohen, Deborah A.; Seelam, Rachana; Han, Bing; Arredondo, Elva M.; Castro, Gabriela; Rodriguez, Claudia; Mata, Michael A.; Larson, Anne; Derose, Kathryn P.
Abstract : Churches can be important settings for promoting physical activity (PA) among Latinx populations. Little is known about what factors across the church context—social, organizational, and physical (outdoor spaces)—are associated with Latinx PA to inform faith-based PA interventions. This study investigated associations of church contextual factors with Latinx PA. We used cross-sectional data from a Latinx adult sample recruited from 6 churches that each had a nearby park in Los Angeles, California (n = 373). Linear or logistic regression models examined associations of church PA social support, PA social norms, perceived quality and concerns about the park near one's church, and church PA programming with 4 outcomes: accelerometer-based moderate-to-vigorous PA (MVPA) and self-reported adherence to PA recommendations, use of the park near one's church, and park-based PA. Park quality and concerns were positively associated with using the park near one's church. Church PA programming was positively associated with park-based PA. None of the factors were related to accelerometer-based MVPA or meeting PA recommendations. Findings suggest targeting church PA programming and nearby parks may be key to improving Latinx park use. Church and local parks department partnerships may help enhance park conditions to support churchgoing Latinx PA and health.